2014
DOI: 10.1007/s12603-014-0450-3
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia according to the European Working Group on Sarcopenia in Older People (EWGSOP) versus dynapenia as a risk factor for mortality in the elderly

Abstract: The EWGSOP definition of sarcopenia and dynapenia can help to determine risk for mortality and can be used as a screening instrument in public health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(63 citation statements)
references
References 25 publications
4
57
2
Order By: Relevance
“…Most of the studies were performed in Europe (9/17 studies[1927]), while 5 were performed in America (2 in USA, 3 in South America) [2832], and 3 were performed in Asia[3335]. All of the studies included subjects aged 60 years or older; 11 studies included community-dwelling older people[21,22,25,2935], 4 included hospitalized subjects[19,20,24,27], and 2 involved nursing home residents[23,26].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the studies were performed in Europe (9/17 studies[1927]), while 5 were performed in America (2 in USA, 3 in South America) [2832], and 3 were performed in Asia[3335]. All of the studies included subjects aged 60 years or older; 11 studies included community-dwelling older people[21,22,25,2935], 4 included hospitalized subjects[19,20,24,27], and 2 involved nursing home residents[23,26].…”
Section: Resultsmentioning
confidence: 99%
“…Sarcopenia was diagnosed according to the algorithm proposed by the EWGSOP. Muscle mass was measured using bioelectrical impedance analysis (BIA) in the majority of studies (7/17 studies[19,20,2325,27,33]), followed by anthropometric measurements (6/17 studies[21,22,26,2830]) and, finally, by Dual-Energy X-ray Absorptiometry (DXA) (4/17 studies[31,32,34,35]). Muscle strength was measured using handgrip strength in all of studies except for one[35], which used an isokinetic device.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dodds et al , identified low muscle strength in 23% of males and 27% of females by age 80 in more than 60 thousand observations from 49,964 British individuals [11]. Alexandre et al also demonstrated that dynapenia can be common, with prevalences of 29.5% and 41% in two Brazilian samples of 478 and 1149 elders living in the community, respectively [10,28]. …”
Section: Discussionmentioning
confidence: 99%
“…Manini and Clark propose that there is still a work in progress in the definition of an algorithm specific for dynapenia, arguing that, among other things, there is insufficient data to define clinically relevant cut points for muscle strength [9], and different points lead to different dynapenia prevalence. Alexandre et al evidenced the association of dynapenia with mortality in an elderly population of a large Brazilian city using the cut-off suggested by the European group EWGSOP (cut-off values < 30 kg for men and < 20 for women) [10]. Dodds et al defined low grip strength as the strength at least 2.5 SD below the mean gender- specific peak and established normative data for dynapenia combining more than 60 thousand observations [11].…”
Section: Introductionmentioning
confidence: 99%